Strategy for Strengthening Social Safety Nets for the People of Pangkalpinang City in the Covid-19 Pandemic Era - Ramadhani, Tiara; Sinabutar, Michael Jeffri; Zulkarnain, Iskandar; Rahman, Bustami (Future Science)
This study aims to identify and analyze strategies for strengthening social safety nets for the people of Pangkalpinang City in the Covid-19 Pandemic Era. Pangkalpinang City is an area with a fairly dense population. With a population of 218,569 people. Meanwhile, the number of poor people in 2020 is 9.40 thousand people. With a fairly large number of poor people and the current situation of the COVID-19 pandemic, the Pangkalpinang City Government must be prepared to face various threats that endanger the national economy, especially the economy of the people of Pangkalpinang City. One of the strategies issued by the Government is through the Social Safety Net which aims to maintain people's purchasing power which is manifested in the form of social assistance. The social safety net provided by the Government for the community consists of 2 (two) types, namely cash deposit assistance (BST) and basic food programs (non-cash). The basic food program is the provision of social assistance to poor and vulnerable families to reduce the burden of meeting food needs. Meanwhile, cash deposit assistance is social assistance provided in the form of cash, which is disbursed through the post office. The recipients of this social assistance are people who are registered as poor people. The amount of social assistance received by the community is Rp. 600,000 for 3 months and Rp. 200,000. people who receive social assistance can only choose one program. The data collection technique was carried out using the literature review method. Meanwhile, the data analysis technique is carried out with the stages of collecting, reducing, displaying and drawing conclusions.